MENGATASI KENAKALAN SISWA MELALUI PENDIDIKAN KARAKTER GUNA MENINGKATKAN KEAKTIFAN BELAJAR SISWA - Yulianti Tampang; Viviliana Pare Sulo; Jevita Jevita; Merlin Bangun (CV. Adiba Aisha Amira, 2023)
The birth of globalization was influenced by developments in technology and science to make relations between nations and countries more open. Therefore, the values, norms and culture of a nation can be easily accepted by other nations. The other impact of this development is that modernization and industrialization besides providing benefits also include excesses of harm to human life. In the world of education there are also many changes and transitions that are increasingly closely related to technological advances, especially materials. Education that is increasingly broad to be studied and easily all of that can be accessed by exploring cyberspace. This research uses a qualitative approach and literature study. Student delinquency is a change in the character of a learner in an incorrect direction so that the standard rules that apply at school are not in line with the character of a student. The result of this study is that there needs to be a special approach to students.